Russia and the USA - Hudolej, Konstantin Konstantinovič (Teorija in praksa, 2019)
In recent years Russian-American relations have seen a significant deterioration. However, the resulting confrontation is not as great in either scope or the level of intensity that existed during the Cold War. Although contradictions between Russia and the United States are significant, they are not antagonistic. The opposition on global issues is on the whole manageable, but could intensify if the system of treaties and arms control continues to erode, particularly due to the growing competition in cyberspace. Regional conflicts have an even greater negative impact on Russia-US relations, although almost all of them are on the periphery of world politics. An improvement in Russian-American relations is hardly possible in the immediate future, yet a sharp return to the Cold War level is also unlikely. The continuation of a "Cool War" - limited confrontation - seems the most likely scenario.
Keywords: Cold war; Hladna vojna; International conflicts; International relations; Mednarodni konflikti; Mednarodni odnosi